2015
DOI: 10.1002/hep.28024
|View full text |Cite
|
Sign up to set email alerts
|

Jagged1 heterozygosity in mice results in a congenital cholangiopathy which is reversed by concomitant deletion of one copy of Poglut1 (Rumi)

Abstract: Haploinsufficiency for the Notch ligand JAG1 in humans results in an autosomal dominant, multisystem disorder known as Alagille syndrome, which is characterized by a congenital cholangiopathy of variable severity. Here we show that on a C57BL/6 background, jagged1 heterozygous mice (Jag1+/−) exhibit impaired intrahepatic bile duct (IHBD) development, decreased SOX9 expression and thinning of the peri-portal vascular smooth muscle cell (VSMC) layer, which are apparent at embryonic day 18 and the first postnatal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

10
133
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 85 publications
(144 citation statements)
references
References 48 publications
10
133
0
1
Order By: Relevance
“…Since some ALGS subjects have a deletion of the entire JAG1 gene (24)(25)(26), others have concluded that ALGS pathology results from JAG1 haploinsufficiency. The appearance of a cholangiopathy in JAG1 +/-heterozygous-knockout mice led to the same conclusion (23). However, haploinsufficient (Jag1 +/-) mice do not develop liver pathology (21,22).…”
Section: Discussionmentioning
confidence: 77%
See 1 more Smart Citation
“…Since some ALGS subjects have a deletion of the entire JAG1 gene (24)(25)(26), others have concluded that ALGS pathology results from JAG1 haploinsufficiency. The appearance of a cholangiopathy in JAG1 +/-heterozygous-knockout mice led to the same conclusion (23). However, haploinsufficient (Jag1 +/-) mice do not develop liver pathology (21,22).…”
Section: Discussionmentioning
confidence: 77%
“…Defects in bile duct development were only noted only after a mutation at another genetic locus within the Notch signaling pathway (Notch2 +/-) was bred into the Jag1 +/-mice (21). In another murine study, bile duct paucity only developed after Jag1 +/-heterozygosity was placed on a particular murine genetic background (23). The requirement for a particular strain background also indicates that another genetic factor (i.e., within the permissive strain background) was required for liver disease to develop in Jag +/-haploinsufficient mice.…”
Section: Discussionmentioning
confidence: 98%
“…This consensus motif is highly predictive of enzymatic modification, as mass spectrometric analyses have demonstrated that most if not all EGF repeats with a CXSX(P/A)C motif examined so far are O-glucosylated (Hase et al, 1988;Acar et al, 2008;Fernandez-Valdivia et al, 2011;Rana et al, 2011;Lee et al, 2013;Haltom et al, 2014;Ramkumar et al, 2015;Thakurdas et al, 2016). Agrin, which is implicated in muscle disease, is predicted to have a single POGLUT1 target site.…”
Section: D233ementioning
confidence: 99%
“…Among the confirmed POGLUT1 biochemical targets, Drosophila Notch, mouse Notch1, mouse CRUMBS2, and Drosophila Eyes shut are shown to be functionally regulated by POGLUT1-mediated glycosylation (Acar et al, 2008;Fernandez-Valdivia et al, 2011;Leonardi et al, 2011;Haltom et al, 2014;Ramkumar et al, 2015). Moreover, there is evidence suggesting that mouse JAG1 might also be a biologically relevant target of POGLUT1, although further experiments are required to prove this (Thakurdas et al, 2016). Based on the severe decrease in Notch signaling and Notch1 cleavage in our patients' muscle, the dramatic decrease in the ability of POGLUT1 D233E to glycosylate Notch EGF repeats, and previous observations on the role of POGLUT1 and Notch receptor O-glucosylation in Notch signaling (Acar et al, 2008;Fernandez-Valdivia et al, 2011;Leonardi et al, 2011;Ma et al, 2011;Rana et al, 2011), we propose that the Notch receptors are the key target of POGLUT1 in the muscle.…”
Section: D233ementioning
confidence: 99%
“…O-Glucosylation is also essential for Notch function in flies because loss of rumi in flies results in temperature-sensitive Notch-null phenotypes (29,30). Loss of mouse Poglut1 also results in a severe decrease in NOTCH1 signaling in embryos and several cell lines (30,31), although POGLUT1 does not seem to be essential for NOTCH2 signaling during liver development (32). O-Glucose can also be extended to Xyl␣1-3Glc␤-O-Ser by glucoside ␣3-xylosyltransferases (Shams in flies and GXYLT1 and GXYLT2 in mammals) (33,34).…”
mentioning
confidence: 99%